2008
DOI: 10.1093/geront/48.1.105
|View full text |Cite
|
Sign up to set email alerts
|

BE-ACTIV: A Staff-Assisted Behavioral Intervention for Depression in Nursing Homes

Abstract: Because depression among nursing home residents is prevalent, heterogeneous, and often treatment resistant, there is a need for effective, low-cost interventions that are ecologically acceptable and efficient. BE-ACTIV is a promising intervention; it is brief, addresses institutional barriers, involves facility staff in treatment, and is acceptable to residents. As such, BE-ACTIV merits further evaluation to establish efficacy and effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 26 publications
3
75
3
4
Order By: Relevance
“…Studies in the community included outpatient clinics (Acierno et al, 2012;Bottonari, Roberts, Thomas, & Read, 2008;Gallagher & Thompson, 1982;Lazzari, Egan, & Rees, 2011;Rokke, Tomhave, & Jocic, 1999;Thompson, Gallagher, & Breckenridge, 1987;Turner & Leach, 2009) and the client's home (Quijano et al, 2007;Teri, Logsdon, Uomoto, & McCurry, 1997;Yon & Scogin, 2009). Studies in residential care settings included assisted living (Cernin & Lichtenberg, 2009;Dozeman et al, 2011), nursing homes (Meeks, Looney, Van Haitsma, & Teri, 2008;Meeks, Teri, Van Haitsma, & Looney, 2006), a shortterm rehabilitation unit (Sood, Cisek, Zimmerman, Zaleski, & Fillmore, 2003), and inpatient psychiatric care facilities (Clignet, Van Meijel, Van Straten, Lampe, & Cuijpers, 2012;Snarski et al, 2011).…”
Section: Participant and Setting Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies in the community included outpatient clinics (Acierno et al, 2012;Bottonari, Roberts, Thomas, & Read, 2008;Gallagher & Thompson, 1982;Lazzari, Egan, & Rees, 2011;Rokke, Tomhave, & Jocic, 1999;Thompson, Gallagher, & Breckenridge, 1987;Turner & Leach, 2009) and the client's home (Quijano et al, 2007;Teri, Logsdon, Uomoto, & McCurry, 1997;Yon & Scogin, 2009). Studies in residential care settings included assisted living (Cernin & Lichtenberg, 2009;Dozeman et al, 2011), nursing homes (Meeks, Looney, Van Haitsma, & Teri, 2008;Meeks, Teri, Van Haitsma, & Looney, 2006), a shortterm rehabilitation unit (Sood, Cisek, Zimmerman, Zaleski, & Fillmore, 2003), and inpatient psychiatric care facilities (Clignet, Van Meijel, Van Straten, Lampe, & Cuijpers, 2012;Snarski et al, 2011).…”
Section: Participant and Setting Characteristicsmentioning
confidence: 99%
“…Several studies demonstrated the successful implementation of behavioral activation interventions by nonmental-health professionals such as case managers (Quijano et al, 2007), occupational therapists (Sood et al, 2003), residential care staff (Cernin & Lichtenberg, 2009;Dozeman et al, 2011;Meeks et al, 2006Meeks et al, , 2008, and family caregivers (Teri et al, 1997). Acierno et al (2012) showed that individuals with varied levels of training and expertise (ranging from recent graduates of bachelor programs in psychology to experienced social workers) were able to implement behavioral activation.…”
Section: Participant and Setting Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations